Global priorities for conservation of reptilian phylogenetic diversity in the face of human impacts - Gumbs, Rikki; Gray, Claudia L.; Böhm, Monika; Hoffmann, Michael; Grenyer, Richard; Jetz, Walter; Meiri, Shai; Roll, Uri; Owen, Nisha R.; Rosindell, James (Nature communications, 2020)
Phylogenetic diversity measures are increasingly used in conservation planning to represent aspects of biodiversity beyond that captured by species richness. Here we develop two new metrics that combine phylogenetic diversity and the extent of human pressure across the spatial distribution of species — one metric valuing regions and another prioritising species. We evaluate these metrics for reptiles, which have been largely neglected in previous studies, and contrast these results with equivalent calculations for all terrestrial vertebrate groups. We find that regions under high human pressure coincide with the most irreplaceable areas of reptilian diversity, and more than expected by chance. The highest priority reptile species score far above the top mammal and bird species, and reptiles include a disproportionate number of species with insufficient extinction risk data. Data Deficient species are, in terms of our species-level metric, comparable to Critically Endangered species and therefore may require urgent conservation attention. In addition to species richness, evolutionary measures of biodiversity are important considerations for conservation. Here, Gumbs et al. develop new biodiversity metrics incorporating phylogenetic diversity and human pressure and highlight conservation priorities in a global analysis of reptiles.